Mass spectrometric measurement of hydrogen isotope fractionation for the reactions of chloromethane with OH and Cl - Keppler, Frank; Greule, Markus; Schöler, Heinz Friedrich (Atmospheric chemistry and physics, 2018)
Abstract. Chloromethane (CH3Cl) is an important provider of chlorine to the stratosphere but detailed knowledge of its budget is missing. Stable isotope analysis is a potentially powerful tool to constrain CH3Cl flux estimates. The largest degree of isotope fractionation is expected to occur for deuterium in CH3Cl in the hydrogen abstraction reactions with its main sink reactant tropospheric OH and its minor sink reactant Cl atoms. We determined the isotope fractionation by stable hydrogen isotope analysis of the fraction of CH3Cl remaining after reaction with hydroxyl and chlorine radicals in a 3.5 m3 Teflon smog chamber at 293 ± 1 K. We measured the stable hydrogen isotope values of the unreacted CH3Cl using compound-specific thermal conversion isotope ratio mass spectrometry. The isotope fractionations of CH3Cl for the reactions with hydroxyl and chlorine radicals were found to be -264±45<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="43b54b1a4760b2ad7bc64caa4dcf2d19"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-18-6625-2018-ie00001.svg" width="52pt" height="10pt" src="acp-18-6625-2018-ie00001.png"/></svg:svg> and -280±11<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="52pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="62d70adff0e7afd0390fdc4d52c372b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-18-6625-2018-ie00002.svg" width="52pt" height="10pt" src="acp-18-6625-2018-ie00002.png"/></svg:svg> ‰, respectively. For comparison, we performed similar experiments using methane (CH4) as the target compound with OH and obtained a fractionation constant of -205±6<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="46pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="c22901eed2f7ed27e67c7076a8f4bad7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-18-6625-2018-ie00003.svg" width="46pt" height="10pt" src="acp-18-6625-2018-ie00003.png"/></svg:svg> ‰ which is in good agreement with values previously reported. The observed large kinetic isotope effects are helpful when employing isotopic analyses of CH3Cl in the atmosphere to improve our knowledge of its atmospheric budget.
Gesehen am 05.09.2019